Biology of Breeding Poultry: Poultry Science Symposium Series Volume twenty-nine - Hocking, P.M (CABI, 2014)
Commercial broilers, turkeys and ducks are largely the products of 50 years of organized genetic selection for growth, feed efficiency and carcass yields in North America and Western Europe. This process has revolutionized the poultry industry and resulted in the efficient worldwide production of nutritious and healthy meat for the consumer. The intensive production of poultry meat continues to expand in many parts of the world, particularly in the emerging economies of Brazil, China and India. Chicks, poults and ducklings necessarily require adult male and female birds that are also required to reproduce efficiently. Adults of current meat breeding lines are so radically changed from traditional lines that gave rise to them that an essentially new class of farm livestock has been produced. The high growth rates of these birds lead inevitably to high adult body weights, which have also affected the reproductive systems of females and the mating efficiency of males. The management and husbandry systems for breeding birds have also developed in parallel with the genetic changes, and a review of the current scientific knowledge of these birds is both timely and opportune. This book contains reviews of the literature pertaining to breeding poultry of the three main poultry species (broiler, turkey and duck) and a chapter on minor species for which there is some information (Chapter 16). Typically these birds are fed on cereal-based diets and are housed on deep litter with various standards of environmental control, depending on the climate and region. The broiler chicken is probably more advanced genetically than any other species, and in general the husbandry and management of the other species are based on the broiler chicken model. There is relatively little published information on the duck and even less on geese, both of which are kept in some countries with access to water for swimming and green plant material as a feed. Geese are not commonly kept in large intensive operations or indoors, and Romanov (1999) has reviewed the available literature. Ducks are also kept for the production of foie gras in France, and further information is available in the report by Guemene and Guy (2004)